1978
DOI: 10.1021/bi00605a028
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman studies of bovine metarhodopsin I and metarhodopsin II

Abstract: The resonance Raman spectra of bovine metarhodopsin I and metarhodopsin II have been measured. The spectra are compared with model chromophore resonance Raman data. It was found that metarhodopsin I is linked to opsin via a protonated Schiff base linkage, whereas metarhodopsin II is linked by an unprotonated Schiff base. A recent suggestion that the chromophore of metarhodopsin II is retinal is explicitly disproved. The chromophores of both metarhodopsins are found to have an essentially all-trans conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
156
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 16 publications
(37 reference statements)
13
156
1
Order By: Relevance
“…The "time scale" of the pulsed experiment is not dictated by the pulse duration but by the light intensity, because the light-dependent rates are so much larger than the light-independent rates. Doukas et al (16) have shown that metarhodopsin I does not exhibit these low wavenumber lines and looks like an all-trans chromophore. Therefore, Raman measurements of the conversion of bathorhodopsin lumirhodopsin and lumirhodopsin -metarhodopsin I should provide evidence concerning the origin of these unique bathorhodopsin lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The "time scale" of the pulsed experiment is not dictated by the pulse duration but by the light intensity, because the light-dependent rates are so much larger than the light-independent rates. Doukas et al (16) have shown that metarhodopsin I does not exhibit these low wavenumber lines and looks like an all-trans chromophore. Therefore, Raman measurements of the conversion of bathorhodopsin lumirhodopsin and lumirhodopsin -metarhodopsin I should provide evidence concerning the origin of these unique bathorhodopsin lines.…”
Section: Resultsmentioning
confidence: 99%
“…Second, selective resonance enhancement permits the assignment of particular Raman lines to specific molecules in the photostationary steady state (5). These experiments have already been used to examine the conformation and interactions of the retinal chromophore in rhodopsin, isorhodopsin, and several of their photolytic intermediates (5,(12)(13)(14)(15)(16). One objective of this study was to obtain a spectrum of bathorhodopsin that would provide information on the strength of the C=N bond at the C-15 position and on the degree of protonation of the Schiff base nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate these latter residues act in catalysis as water activators or proton donors/acceptors because the hydrolysis reaction requires Schiff base protonation to occur efficiently. This point leads to an interesting question; how can Schiff base hydrolysis even occur in MII rhodopsin, since a protonated Schiff base is not detected for rhodopsin by vibrational spectroscopy (22,68,69)? There are two likely possibilities: (i) protonation is transient and followed by rapid hydrolysis, or (ii) a small population of MII rhodopsin may exist in the protonated form that is not resolved by the above mentioned techniques.…”
Section: Deuteruim Isotope Studies Support That a Tetrahedral Carbinomentioning
confidence: 99%
“…Thus the v(C = ND) represents an almost 'pure' C = N vibration. The v(C = NH) bands are Table 1 Summary of peak positions (given in cm-') of the v(C = N) mode in H,O and D20, the y(C-N-D) and the v(C = C)' vibrations [25][26][27][28][29] 700 800 900 1000 1100 1200 1300 1400 1500 1600 1700…”
Section: Spectra Of the Initial Statesmentioning
confidence: 99%